2021
DOI: 10.3390/cancers13040929
|View full text |Cite
|
Sign up to set email alerts
|

Germline and Somatic Whole-Exome Sequencing Identifies New Candidate Genes Involved in Familial Predisposition to Serrated Polyposis Syndrome

Abstract: The serrated polyposis syndrome (SPS) is the most common and yet underdiagnosed colorectal polyposis syndrome. It is characterized by multiple and/or large colonic serrated polyps and a higher associated risk for colorectal cancer (CRC). The main objective of this study was to identify new candidate genes involved in the germline predisposition to SPS/CRC. Thirty-nine SPS patients from 16 families (≥2 patients per family) were recruited without alterations in well-known hereditary CRC genes, and germline and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…The single-base substitution (SBS) signatures SBS.1 and SBS.5, considered clock-like mutational signatures, were the most represented in both samples, and no other distinctive signature was apparent. 24 In a validation SPS cohort of 211 unrelated patients, gene panel sequencing revealed four additional rare, missense variants in WNK2 including c.2105C>T (p.Pro702Leu) in PanSPS_044, c.2792C>T (p.Thr931Met) in PanSPS_095, c.3341C>T (p.Thr1114Met) in PanSPS_078 and c.5588T>C (p.Leu1863Pro) in PanSPS_055. The c.2792C>T variant was detected in a male SPS patient (onset at 67 years) in a family where an additional sample for variant segregation was available.…”
Section: Resultsmentioning
confidence: 99%
“…The single-base substitution (SBS) signatures SBS.1 and SBS.5, considered clock-like mutational signatures, were the most represented in both samples, and no other distinctive signature was apparent. 24 In a validation SPS cohort of 211 unrelated patients, gene panel sequencing revealed four additional rare, missense variants in WNK2 including c.2105C>T (p.Pro702Leu) in PanSPS_044, c.2792C>T (p.Thr931Met) in PanSPS_095, c.3341C>T (p.Thr1114Met) in PanSPS_078 and c.5588T>C (p.Leu1863Pro) in PanSPS_055. The c.2792C>T variant was detected in a male SPS patient (onset at 67 years) in a family where an additional sample for variant segregation was available.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the efforts to study CRC heterogeneity, our current knowledge in this field is just the tip of the iceberg. Expanding next-generation sequencing (NGS), single-cell sequencing, and whole-exome sequencing techniques along with the application of omics data at various levels, including genomics, epigenomics, transcriptomics, peptidomics, proteinomics, and metabolomics, could give us valuable information on the heterogeneity of CRCs (116)(117)(118)(119)(120)(121)(122)(123).…”
Section: Heterogeneity Assessment Methodsmentioning
confidence: 99%
“…Another recent study identified 14 polymorphic variants involved in familial predisposition to serrated polyposis syndrome, a condition in which colorectal polyps are highly susceptible to progression to adenocarcinomas. Of the 14 polymorphic variants identified, 2 of the 14 were found in CFTR [ 42 ].…”
Section: Involvement Of Cftr In Gi Cancersmentioning
confidence: 99%
“…Germline heterozygous carriers of specific CFTR polymorphic variants are also at a higher risk for CRC, including in young adults [ 41 ] and in patients with familial serrated polyposis syndrome [ 42 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation